Effect of a virtual reality program on patient comfort in the surgical intensive care unit of a French university hospital: study protocol for a monocentric, prospective, superiority, randomised controlled trial–ZION study - Osama Abou-Arab; Pierre Huette; Guillaume Haye; Mathieu Guilbart; Momar Diouf; Christophe Beyls; Herve Dupont; Yazine Mahjoub; Jonathan Meynier; Thomas Lefebvre; Azrat Ibrahima; Guillaume Bayart; et al. (BMJ Open)
Introduction Admission to a surgical intensive care unit (ICU) following major surgery is associated with a number of discomforts, not only related to the disease itself but also to the care provided or the ICU environment itself (lights, sounds, pain, sleep deprivation, thirst, etc). This discomfort is real and can be associated with psychological consequences. We hypothesised that the use of immersive virtual reality (IVR) with HypnoVR is feasible and can help reduce discomfort in intensive care.Methods and analysis The ZION trial is a prospective, monocentric trial randomising 194 patients admitted to a surgical ICU after a major surgery. The inclusion criterion is patients admitted to a surgical ICU for at least 48 hours following major surgery (cardiac, thoracic or major abdominal surgery). Patients will be allocated to the intervention group (n=97) or the control group (n=97). In the intervention group, patients will receive IVR using HypnoVR two times a day during the ICU stay (2–5 days). In the control group, postoperative care will be conducted according to standard care without IVR. The primary endpoint will be the 18-item IPREA (Inconforts des Patients de REAnimation) questionnaire on the day of ICU discharge. The secondary endpoints will include intensity of discomfort symptoms (anxiety, pain, dyspnoea, thirst and sleep deprivation); the 18-Item IPREA Questionnaire assessed daily from randomisation to the V1 follow-up visit (ICU discharge); incidence of delirium; cumulative morphine consumption at ICU discharge; length of ICU stay and anxiety or depression at 1 month after discharge from intensive care and patient experience of device use.Ethics and dissemination Ethical approval was obtained from the institutional review board of the University Hospital of Amiens (Registration number ID: 2024-A01528-39) in January 2025.Trial registration number NCT06830369.